The Objective Lens: An Analytical Study Of D.H. Lawrence's Short Stories (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper delves into the distinctive narrative strategies, themes, and stylistic elements that characterize D.H. Lawrence's short stories. Through an analytical lens, the study explores how Lawrence's writing reflects the psychological complexity of characters, his critique of societal norms, and the use of nature as a metaphor for human experiences. The paper draws on major short stories, including "The Rocking-Horse Winner," "The Horse Dealer's Daughter," and "The Prussian Officer," to examine the interplay between individual consciousness and external forces in shaping human identity. Ultimately, this study aims to demonstrate how Lawrence’s short stories provide profound insights into the human condition and the tensions between instinct, social constraints, and the quest for fulfillment.